2001
DOI: 10.1207/s15327914nc41-1&2_10
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventive Effects of Soy Protein and Purified Soy Isoflavones on DMBA-Induced Mammary Tumors in Female Sprague-Dawley Rats

Abstract: There are conflicting reports on the effect of soy and its components on mammary carcinogenesis in adult female rats, mainly because of different rodent models that are used in chemoprevention studies. The present study was undertaken to compare the tumor-preventative effects of soy protein isolate (SPI) and two of its isoflavones in a "standard" model that had been used for the identification of many chemopreventive agents. Six groups of female Sprague-Dawley rats were provided with modified cornstarch AIN-76… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…However, 1 study showed that soy protein isolate depleted of isoflavones, as well as purified isoflavones, was an effective inhibitor of 7,12-dimethylbenzanthraceneinduced mammary tumors in adult rats. 35 Alternatively, uncontrolled dietary or nondietary factors may have confounded the relationship between total soy product and isoflavone intake and the prevalence of allergic rhinitis. Japanese persons who have a quite high intake of soy products are likely to follow traditional Japanese diet or behaviors that may be preventive against allergic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…However, 1 study showed that soy protein isolate depleted of isoflavones, as well as purified isoflavones, was an effective inhibitor of 7,12-dimethylbenzanthraceneinduced mammary tumors in adult rats. 35 Alternatively, uncontrolled dietary or nondietary factors may have confounded the relationship between total soy product and isoflavone intake and the prevalence of allergic rhinitis. Japanese persons who have a quite high intake of soy products are likely to follow traditional Japanese diet or behaviors that may be preventive against allergic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo genistein and soy protein has been reported to stimulate the growth of implanted MCF-7 xenografts [79,6] whilst other studies have reported anti-tumour effects in such xenografts and in chemically induced mammary cancers [80][81][82]. A review of the literature concluded that in vivo low concentrations of genistein stimulated cell growth but at high concentrations inhibited growth, thus reflecting studies in vitro [67].…”
Section: Phytoestrogens and The Growth Of Oestrogen-dependent Tumoursmentioning
confidence: 99%
“…The development of drug resistance has encouraged the development and testing of new antiestrogens for the treatment of breast cancer. Because of its tissue-specific antiestrogenic/estrogenic properties, genistein has been considered a natural selective estrogen receptor modulator [13][14][15].…”
Section: Investigators Havementioning
confidence: 99%